Evaluation of dissolved oxygen sinks in water-stirring setups used in reaeration experiments. (8th March 2022) - Ferreira, M. de S.; da Luz, M. S.; Silveira, A.; Pinheiro, H. D.; Gonçalves, J. C. de S. I.
Abstract: Dissolved oxygen (DO) is an essential parameter of water quality, and the surface reaeration process (K2 ) is the main source of DO in aquatic ecosystems. On a laboratory scale, reaeration measurements are performed using water-stirring setups (WSSs), but possible physical DO sinks are not considered in the WSSs. This paper aimed to assess the presence of physical DO sinks in WSSs. The experiments were carried out in four WSSs: circular hydraulic channel (CHC); straight hydraulic channel (SHC); turbine-stirred tank (TST); and oscillating grid tank (OGT). The physical DO sink was estimated by inserting a first-order term (K3, day −1 ) in the classic equation of DO balance. All WSSs presented physical DO sinks during the reaeration experiments: SHC (mean K3 = 4.58 day −1 ) > TST (mean K3 = 1.30 day −1 ) > CHC (mean K3 = 1.12 day −1 ) > OGT (mean K3 = 0.13 day −1 ). Physical DO sinks were originated from low-pressure zones located in WSSs, which was confirmed by the negative correlation (r = −0.78) between K3 and the static pressure in the suction pipeline of the SHC. This study presented additional information about identifying, and quantifying, physical DO sinks in WSSs, which are essential to produce a correct estimation of the K2 . HIGHLIGHT: Water-stirring setups can produce a physical DO sink in reaeration experiments; physical DO sink intensity depends on the size and type of the water-stirring structure; physical DO sink is associated with low-pressure zones in the water-stirring setups.